Estratégias de agricultura de precisão para definição de planos de manejo inteligentes - Silva, Diego Armando Amaro da (2016)
This study used precision agriculture (AP) techniques to understand the dynamics of physical, chemical and biological soil for different winter management systems after three years of cultivation, to serve as the basis of the definition and indication of Intelligent Management Plans (PMI) in an efficient and practical way. The work was conducted in the city of Frederico Westphalen, RS, were evaluated ten winter management systems - fallow (PO), wild oat (Ap), white oat (AB), ryegrass (AZ), forage turnip (NF) vetch (E), white lupine (TB) and consortiums ApNFE, ApNF and ApE - with samples collected at the intersection points of a grid of 5 x 2.5 m, totaling 100 sampling points, so that there were ten points by sampling winter management system. The study was based on the evaluation of the effects of systems on the dynamics of spatial and horizontal distribution of physical, chemical and biological indicators of soil quality, an integrated analysis by proposing a soil quality index (IQS), providing support for future directions of PMI. In addition, it assessed the efficiency of the normalized difference vegetation index (NDVI) for estimating the production of the dry matter of winter management systems in order to provide a practical tool to assist in monitoring the operation of selected systems. The tools provided by AP facilitate the understanding of the dynamics of soil quality indicators in the tested systems, serving as a valuable tool in the definition and indication of PMI, providing greater knowledge of the ecology and behavior of soil biology, being possible to determine soil quality bioindicators. Based on the results, not recommended to opt for a system based in isolated benefits (indicators), requiring the joint evaluation of the variables, which was facilitated by the proposed IQS. In general, the systems that provide soil quality were ApNFE, ApE and NF, highlighting the facilitated root growth, in addition to greater nutrient supply afforded by these systems. The use of grass monocultures causes deterioration of chemical properties, due to low C/N and C/P ratios these systems, acting as nutrients immobilizers, must be rotated or consorted with other species over the years. The PO should be avoided in practice or even extinct, based on physical and biological degradation provided by this system. The NDVI was able to determine the dry matter produced by cover crops, except systems with visible flowers or consorted. The objectives proposed by this study were considered solved, since the answers obtained in the articles proposed by the latter, in order to make the multi-plant management or PMI proposition, more grounded and specialized.